2018
DOI: 10.1186/s12900-018-0084-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure activity relationship (SAR) and quantitative structure activity relationship (QSAR) studies showed plant flavonoids as potential inhibitors of dengue NS2B-NS3 protease

Abstract: BackgroundDue to dengue virus disease, half of the world population is at severe health risk. Viral encoded NS2B-NS3 protease complex causes cleavage in the nonstructural region of the viral polyprotein. The cleavage is essentially required for fully functional viral protein. It has already been reported that if function of NS2B-NS3 complex is disrupted, viral replication is inhibited. Therefore, the NS2B-NS3 is a well-characterized target for designing antiviral drug.ResultsIn this study docking analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 26 publications
3
32
0
Order By: Relevance
“…Flavones are dual fused aromatic rings (A and C) with an extension of a benzene ring (B) at position 2 of ring C (Figure 3) [87]. The skeleton "ring A fused with ring C" has previously reported to possess antiviral activity against the dengue virus NS2B-NS3 complex [88]. Moreover, hydroxylation on ring A, particularly on positions 5 and 7, was found to be favorable for antiviral activity against the influenza A virus [89].…”
Section: Structure-activity Relationship Among Potential Antiviral Flmentioning
confidence: 99%
“…Flavones are dual fused aromatic rings (A and C) with an extension of a benzene ring (B) at position 2 of ring C (Figure 3) [87]. The skeleton "ring A fused with ring C" has previously reported to possess antiviral activity against the dengue virus NS2B-NS3 complex [88]. Moreover, hydroxylation on ring A, particularly on positions 5 and 7, was found to be favorable for antiviral activity against the influenza A virus [89].…”
Section: Structure-activity Relationship Among Potential Antiviral Flmentioning
confidence: 99%
“…The present study emphasizes on the modeling of receptor binding domain (RBD) of nCoV-SP and generating a stable protein model which puts insight into its structure for possible interaction study of the protein with our choice of inhibitors and binds to the possible important residues of RBD that are crucial in interaction with the human receptor and further viral entry into the cell and pathogenesis. Flavonoids with its broad biological activity including antiviral activity against other viruses as well as SARS [33][34][35][36][37][38][39][40][41][42][43][44] were taken under consideration in this study, as molecular works of flavonoids against SARS-CoV and SARS-CoV-2 have not been done yet.…”
Section: Discussionmentioning
confidence: 99%
“…Different flavonoids with antioxidant, hepatoprotective, antibacterial, anti-inflammatory, anticancer and antiviral properties from different literatures were considered [15][16]. Flavonoids possessing antiviral activity against some viruses including coronavirus were also taken into consideration [33][34][35][36][37][38][39][40][41][42][43][44]. However, no study on the molecular level of flavonoids has been reported against nCoV-SP and, hence, flavonoids were considered in this computational study against For better reliability and precise results two docking software, PyRx [45] and iGEMDOCK [46] (N=800), 80 generation and 10 solutions were carried out with our choice of ligands in iGEMDOCK against both the protein models [47,48].…”
Section: Ligand Selection and Ligand File Preparationmentioning
confidence: 99%
“…Hence, to overcome such situation presently, available more resources, much faster, and advance scientific techniques need to be adopted and explored. Earlier, a number of studies have proposed various traditional and specific methods for the identification of different chemical entities and demonstrated their selective inhibition mechanism and inhibitory efficacy against NS3‐NS2B protease complex at different levels …”
Section: Introductionmentioning
confidence: 99%